Electrochemical Redox Cycling Realized by Chromatography Paper-based Sensor - Kenichi Fukayama; Sou Yamamoto; Shigeyasu Uno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
In this work, we demonstrated that enhancement of electrochemical current due to redox cycling could be accomplished by paper-based biosensor without any expensive micro-fabrication process. The paper-based sensor had layered structure to generate higher current than a conventional one. We took advantage of the fact that the paper thickness was micrometer-sized (180um), and it defined the distance between two electrochemical electrodes on both sides of the paper. Experimental results showed signatures of the redox cycling, where the electrochemical current from low concentration molecules could be arbitrarily increased by decreasing the distance between electrodes. Such a structure was advantageous for detecting target molecules at very low concentration, proposing a low-cost highly-sensitive biochemcal sensor.